Enhancement of Q(m) by co-doping of Li and Cu to potassium sodium niobate lead-free ceramics - Li, E (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2008)
Lead-free piezoelectric ceramics KNN modified by Li-substitution and CuO addition have been synthesized, and the piezoelectric and dielectric properties were measured. A morphotropic phase boundary (MPB) between orthorhombic and tetragonal phases was formed with Li-substitution. The co doping of Li and Cu markedly enhanced the mechanical quality factor (Q(m)) in comparison with the sole doping of Li and Cu. Anomalous anti ferroelectric-like hysteresis curves were observed in 2 mol% CuO-doped ceramics. The anti-ferroelectric-like curves were changed to that of normal ferroelectrics following poling. A model based on the formation of the internal bias field (Ei) due to the movements of space charges was proposed to explain these phenomena. It was considered that the Ei stabilized the spontaneous polarization (Ps) and suppressed the domain wall motion to enhance the Q(m). The highest Qm obtained in this study was 742. The [(Na0(0.5)K0(0.5))(0.96)Li0(0.04) ] NbO(3) + 0.45 mol% CuO ceramics showed a high Q(m) value of 414 with a high piezoelectric constant d(33) of 100 pC/N